Motivation's influence on credit decisions: unveiling the moderating effect of brand awareness in PT Bank Syariah Indonesia Tebing Tinggi branch - Sarwoto, Sarwoto; Cen, Cia Cai; Zalukhu, Rika Surianto; Murni, Sri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The number of MSMEs in Indonesia is very large, but the portion of credit financing to MSMEs is still very small when compared to the percentage of the number of MSMEs. Therefore, this study aims to analyze the effect of MSME customer motivation on credit decisions at PT Bank Syariah Indonesia through brand awareness as a moderating variable. This research is a quantitative descriptive study conducted on 250 MSME customers of PT Bank Syariah Indonesia, who have credit with current status and are willing to be respondents. Sampling method with accidental sampling. This study uses primary data collected by questionnaires distributed to respondents. Respondents' perceptions were measured using a Likert scale.  Research with SEM model, data processing with PLS 3.0 smart software. The results showed that motivation and brand awareness has a significant effect on MSME customer credit decisions at PT Bank Syariah Indonesia Tebing Tinggi branch. Brand awareness can be a moderating variable in the influence of motivation on credit decisions of MSME customers of PT Bank Syariah Indonesia Tebing Tinggi Branch.  The implication of this research is targeting the policy of increasing Islamic bank credit financing that is oriented towards brand awareness.